2017
DOI: 10.5194/acp-17-5865-2017
|View full text |Cite
|
Sign up to set email alerts
|

How does sea ice influence <i>δ</i><sup>18</sup>O of Arctic precipitation?

Abstract: Abstract. This study investigates how variations in Arctic sea ice and sea surface conditions influence δ 18 O of presentday Arctic precipitation. This is done using the model iso-CAM3, an isotope-equipped version of the National Center for Atmospheric Research Community Atmosphere Model version 3. Four sensitivity experiments and one control simulation are performed with prescribed sea surface temperature (SST) and sea ice. Each of the four experiments simulates the atmospheric and isotopic response to Arctic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 41 publications
(56 reference statements)
5
20
0
Order By: Relevance
“…6.2, which showed that the winter-averaged δ 18 O signal correlated with temperatures all over Greenland, resembling the anticorrelations between NEEM δ 18 O and Baffin Bay SIC that have previously been found (Steen-Larsen et al, 2011;Zheng et al, 2018). Moreover, the results are consistent with Faber et al (2017), who found that changes in the Baffin Bay sea ice coverage can impact the δ 18 O precipitation over Greenland (by using an atmospheric general circulation model coupled with water isotopologue tracing (isoCAM3)). Furthermore, the analysis shows only a small patch of correlation between the δ 18 O series and the SIC south of Fram Strait.…”
Section: Sea Ice Concentration and Sea Surface Temperaturesupporting
confidence: 86%
See 2 more Smart Citations
“…6.2, which showed that the winter-averaged δ 18 O signal correlated with temperatures all over Greenland, resembling the anticorrelations between NEEM δ 18 O and Baffin Bay SIC that have previously been found (Steen-Larsen et al, 2011;Zheng et al, 2018). Moreover, the results are consistent with Faber et al (2017), who found that changes in the Baffin Bay sea ice coverage can impact the δ 18 O precipitation over Greenland (by using an atmospheric general circulation model coupled with water isotopologue tracing (isoCAM3)). Furthermore, the analysis shows only a small patch of correlation between the δ 18 O series and the SIC south of Fram Strait.…”
Section: Sea Ice Concentration and Sea Surface Temperaturesupporting
confidence: 86%
“…In order to evaluate this hypothesis, more studies using isotope-enabled modeling are needed. The impact of changes in sea ice on the Arctic δ 18 O precipitation has previously been investigated by Faber et al (2017), who found that the δ 18 O precipitation on Greenland only responded to perturbations of the Baffin Bay sea ice coverage. However, they used a horizontal resolution of ∼ 1.4 • × 1.4 • which barely resolved the Renland Ice Cap of ∼ 1200 km 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distillation and temperature are negatively correlated, and as a result, the modern temperature-δ 2 H precip relationship increases northward along western Greenland, from À0.1‰°C À1 at Kangilinnguit to 3.4‰°C À1 at Thule [IAEA/WMO, 2011] ( Figure S3 in the supporting information). Temperature-δ 2 H precip relationships likely changed through time, as an increase in sea ice cover would increase transport distance and cause more distillation during transport [Jouzel et al, 1997;Faber et al, 2015]. Thus, even if temperature is the main mechanism influencing past δ 2 H precip , records of precipitation isotopes in this region should be used to infer only qualitative changes in temperature, unless independent constraints can be placed on the temperature-δ 2 H precip paleorelationship.…”
Section: 1002/2016gl068513mentioning
confidence: 99%
“…In polar regions, variations in sea ice extent are supposed to affect regional precipitation amounts 20 and to be reflected in the water isotopic composition 21–23 . Current understanding of the impact of sea ice on the vapour isotopic composition is, however, still limited by the number of observations available in sea ice covered areas 24,25 .…”
Section: Introductionmentioning
confidence: 99%